2009
DOI: 10.1111/j.1440-1681.2008.05033.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Short‐term Reproducibility of Arterial Vasoreactivity by Pulse‐wave Analysis After Pharmacological Challenge

Abstract: 1. Pulse-wave analysis (PWA) is an established method to assess arterial wave reflections and arterial vasoreactivity in humans. A high short-term reproducibility of baseline augmentation index (AIx) has been reported. However, the short-term reproducibility of AIx changes following pharmacological challenge with either inhaled salbutamol (endothelium-dependent vasodilatation) or sublingual glyceryl trinitrate (GTN; endothelium-independent vasodilatation), using appropriate statistical methods, is largely unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Our observation that measures of pressure and stiffness differ depending on whether the limb from which they are derived was involved in an exercise stimulus suggest that exercise alters the characteristics of conduit arteries in ways that may compromise the integrity of the GTF. This finding is consistent with a study at rest using applanation tonometry, which found that GTF-derived values became unreliable and had poor reproducibility in response to pharmacologically induced vasodilation using glyceryl trinitrate (9). Despite glyceryl trinitrate having central hemodynamic effects, which we designed our study to avoid, the data of Paul et al (9) nonetheless support our finding that the GTF may be compromised under conditions of altered peripheral function or tone.…”
Section: Discussionsupporting
confidence: 91%
“…Our observation that measures of pressure and stiffness differ depending on whether the limb from which they are derived was involved in an exercise stimulus suggest that exercise alters the characteristics of conduit arteries in ways that may compromise the integrity of the GTF. This finding is consistent with a study at rest using applanation tonometry, which found that GTF-derived values became unreliable and had poor reproducibility in response to pharmacologically induced vasodilation using glyceryl trinitrate (9). Despite glyceryl trinitrate having central hemodynamic effects, which we designed our study to avoid, the data of Paul et al (9) nonetheless support our finding that the GTF may be compromised under conditions of altered peripheral function or tone.…”
Section: Discussionsupporting
confidence: 91%
“…Any valid technique utilised for the measurement of physiological variables must be reproducible [82]. A high intra- and interobserver reproducibility of baseline AIx has been observed in healthy controls and patients with cardiovascular disease and renal dysfunction [7, 38, 8294].…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…A high intra- and interobserver reproducibility of baseline AIx has been observed in healthy controls and patients with cardiovascular disease and renal dysfunction [7, 38, 8294]. Good reproducibility of baseline time to reflection ( T r), an alternative index to AIx, has been reported in several studies [88, 91, 94].…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…The Intraclass Correlation Coefficient (ICC) values for repeated measurements obtained at hourly or weekly intervals have been reported to be 0.72-0.90 for the AIx 2, 13, 14) , which compares favorably with the values (ICC: 0.92-0.97) reported for the carotid-femoral pulse wave velocity [15][16][17] . Unfortunately, few trials have reported the reproducibility of HR-corrected Aix values 2,18,19) ; only one study, as far as we are aware, reported both AIx and AIx@75 2)…”
Section: Reliability Of the Aix And Influence Of Normalization To Hrmentioning
confidence: 99%